Analysis of Annual Plan 1991-92 Education Sector - Planning Commission (Planning Commission Government of India, 1991)
The Analysis of the Annual Plan 1991-92 for the Education Sector provides a comprehensive review of financial allocations, target achievements, and planning strategies in India’s education system. The approved outlay for the year was ₹2,958.22 crores, marking a 14.9% increase over the previous year, with substantial allocations directed toward the Minimum Needs Programme (MNP) for elementary and adult education. The report highlights achievements and shortfalls in enrollment, noting a 27.47 lakh deficit in elementary classes I–V and establishing new targets for Classes I–VIII. State-level analysis indicates full achievement of targets in states such as Uttar Pradesh, Andhra Pradesh, Tamil Nadu, Bihar, and West Bengal, while disparities persist in literacy rates, particularly among females and rural populations, with overall literacy at 52.11% (male: 63.86%, female: 39.47%). Externally aided projects, including the Shiksha Karmi and Bihar Education Projects, supplemented domestic efforts. The analysis underscores the need for strategic financial planning, enhanced monitoring, and targeted interventions to improve enrollment, literacy, and educational equity, serving as a critical resource for the preparation and implementation of the Eighth Five-Year Plan.
Education Division Planning Commission Government Of India Yojana Bhavan, New Delhi October, 1991
Education Division Planning Commission Government Of India Yojana Bhavan, New Delhi October, 1991
Keywords: Annual Plan 1991-92; Education Sector; Elementary Education; Adult Education; Enrollment Targets; Literacy Rates; Minimum Needs Programme; State Achievements; Financial Allocation; Externally Aided Projects; Female Literacy; Educational Planning